Relationship between isokinetic muscle strength and finswimming time - Kunitson, V.; Rannama, I.; Port, K. (LASE Journal of Sport Science, 2013)
Finswimming is a sport, where athlete swims different distances similar to swimming. Divergence comes form that athlete uses one big monofin to produce propulsion. One of the important elements for speed is dependent on the increase of the angular velocity of thigh extension (Rejman 2007). However, there is lack of studies describing role of isokinetic strength on finswimming outcome. Aim of the study was to describe lower limb muscle strength among finswimmers and examine the relationship between isokinetic muscle strength and finswimming time. Methods: eleven top level junior male finswimmers (age 15.7±1.9 yrs., height 177.8±7.8 cm., weight 72.2±9.0 kg) performed 50 m apnea and 200 m finswimming during a high level competition. At the same week isokinetic muscle strength of knee extensors and flexors were measured at angular speeds 60°/s, 180°/s and 240°/s for peak torque, power and total work of 15 repetitions. Results: There was a noticeable correlation between strength of knee extensors on all angular speeds (60°/s, 180°/s, 240°/s) and finswimming time. The data showed strongest correlation r=-0,92 between knee extensors absolute power and 200 m finswimming time at 240°/s. At angular speed of 60°/s there was a strong correlation between peak torque and time r=-0,88. At angular speeds of 60°/s and 180°/s finswimming time was strongly associated (r=-0,85) with power. For 50 m apnea finswimming time a correlation (r=-0,81) was found between power of knee extensors at 180°/s and between peak torque at 60°/s (r=-0.79). All correlations were statistically significant (p<0.05). Correlation between knee flexors and finswimming time was not established. Conclusion: This study suggests that knee extensors strength is related to finswimming time but knee flexors strength does not demonstrate significant impact on finswimming time.